TMSCl as Greener and Effective Solvent for the Synthesis of Carbaryl Derivatives - Satheesh, A.; Rao, J. C. S.; Jayarangarao, P.; Surendra, K.; Usha, H. (Journal of Scientific Research, 2025)
This work introduces a method that is both effective and ecologically sustainable for the production of carbaryl derivatives. Through the utilization of sodium cyanate, phenol/alcohol, and TMSCl (Me3SiCl), a notable level of purity and yield of the synthesized derivatives was attained significantly, this method showcased the efficacy of TMSCl as a gentle, convenient, and effective solvent in supporting this transformation.